2020
DOI: 10.1155/2020/3979482
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Phenotype of Staphylococcus aureus and Escherichia coli Isolates Obtained from Meat in the Formal and Informal Sectors in South Africa

Abstract: Background. Foodborne diseases (FBD) caused by resistant pathogens are a global public health problem. One main driver of the increasing FBD incidence is the transfer of pathogenic organisms from animal guts to carcasses during processing and subsequent transfer from meat products to consumers. Methods. In this study, meat samples from abattoirs in the formal meat sector (FMS) (n=140) and slaughter points in the informal meat sector (IMS) (n=104) were collected for microbial detection and phenotypic AMR determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…This prevalence was considerably higher than the 12% reported in another South African study conducted in 2017 assessing MRSA prevalence in commercial pig herds in the Western Cape, KwaZulu Natal, and Gauteng [ 20 ]. A lower prevalence was also reported in another South Africa study assessing the formal (30%) and informal (50%) meat sectors with isolates obtained from meats samples in abattoirs and slaughtering points [ 21 ]. These differences in prevalence may reflect the sampling framework used.…”
Section: Discussionmentioning
confidence: 80%
“…This prevalence was considerably higher than the 12% reported in another South African study conducted in 2017 assessing MRSA prevalence in commercial pig herds in the Western Cape, KwaZulu Natal, and Gauteng [ 20 ]. A lower prevalence was also reported in another South Africa study assessing the formal (30%) and informal (50%) meat sectors with isolates obtained from meats samples in abattoirs and slaughtering points [ 21 ]. These differences in prevalence may reflect the sampling framework used.…”
Section: Discussionmentioning
confidence: 80%
“…In contrast to the findings of this study, Waters et al [22] reported a 0.00% resistance of S. aureus in US meat and poultry to cloxacillin. The 88.88% resistance to tetracycline is not within the range (25.00 to 82.1%) reported by previous authors [2,8,10,22,26,27,28] though comparable to the 82.10% reported by Jaja et al [2]. This could be due to varied usage of various antibiotic products in each country, as different countries have different products available and registered for use in different species.…”
Section: Resultsmentioning
confidence: 40%
“…This could be due to varied usage of various antibiotic products in each country, as different countries have different products available and registered for use in different species. Varying resistance of S. aureus from raw meat have been reported also by a number of authors, ranging from 25.00% to 73.30% [2,7,26,27,28].…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations